Education for The Improvement of Student Awareness on Cleanliness and Environmental Health - Sudarningsih Sudarningsih; Fahruddin Fahruddin; Tetti Novalina Malik; Ibrahim Ibrahim; Dzikri Dzikri; Ella Rachmawati Dwi Putri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
The results of the situation analysis show that poor hygiene conditions and sanitation facilities that do not comply with health standards occur at SMAIT ANIC, Banjarbaru City, South Kalimantan. Based on the results of this analysis, the Community Partnership Program (PKM) seeks to solve this problem. The PKM program implemented as a solution is education about cleanliness, to increase the school community's knowledge and awareness of the importance of school cleanliness. School cleanliness plays a role in the implementation of education in schools. The method used in the activity is a lecture with questionnaires given before and after the activity as a means of evaluation. This activity also emphasizes active participation from all parties involved, including students and teachers, as well as school administration staff. The results of the activity showed an increase in students' understanding and awareness of the meaning of school cleanliness and sanitation. These results indicate that the objectives of this PKM program have been achieved. Increasing knowledge will certainly have an impact on environmental cleanliness and clean-living habits of students.